Allergy and respiratory health effects of dampness and dampness‐related agents in schools and homes: a cross‐sectional study in Danish pupils. (5th January 2016) - Holst, G. J.; Høst, A.; Doekes, G.; Meyer, H. W.; Madsen, A. M.; Plesner, K. B.; Sigsgaard, T.
Abstract: Little is known about the health effects of school‐related indoor dampness and microbial exposures. In this study, we investigated dampness and dampness‐related agents in both homes and schools and their association with allergy and respiratory health effects in 330 Danish pupils. Classroom dampness was identified based on technical inspection and bedroom dampness on parents' self‐report. Classroom and bedroom dust was analyzed for seven microbial components. Skin prick testing determined atopic sensitization. Lung function was expressed as z ‐scores for forced expiratory volume in one‐second (zFEV1 ), forced vital capacity (zFVC) and the ratio zFEV1 /zFVC using GLI‐2012 prediction equations. The parents reported children's allergies, airway symptoms, and doctor‐diagnosed asthma. High classroom dampness, but not bedroom dampness, was negatively associated with zFEV1 ( β ‐coef. −0.71; 95% CI −1.17 to −0.23) and zFVC ( β ‐coef. −0.52; 95% CI −0.98 to −0.06) and positively with wheezing (OR 8.09; 95% CI 1.49 to 43.97). No consistent findings were found between any individual microbial components or combination of microbial components and health outcomes. Among other indoor risk factors, environmental tobacco smoke (ETS) decreased zFEV1 ( β ‐coef. −0.22; 95% CI −0.42 to −0.02) and zFEV1 /zFVCratio ( β ‐coef. −0.26; 95% CI −0.44 to −0.07) and increased upper airway symptoms (OR 1.66; 95% CI 1.03–2.66). In conclusion, dampness in classrooms may have adverse respiratory health effects in pupils, but microbial agents responsible for this effect remain unknown.